Gärningsmannaskap och medgärningsmannaskap i svensk rätt - Svensson, Erik (Nordisk Tidsskrift for Kriminalvidenskab, 2016)
English title: Perpetration and co-offending in Swedish criminal law The article presents an overview of the conclusions from my dissertation, Gärningsmannaskap vid fleras deltagande i brott, defended at Uppsala University in May 2016. The dissertation examines the concept of perpetration under Swedish law, specifically as the concept concerns the involvement of two or more actors. Three distinct questions are discussed: (i) how the distinction between perpetration of a crime and aiding and/or abetting a crime is to be drawn; (ii) how the distinction between different forms of perpetration should be made in Swedish criminal law; and (iii) in what cases two or more actors can be held criminally liable for having committed a crime together as perpetrators.